Anatomical, histomorphological and molecular classification of cholangiocarcinoma. (20th May 2019) - Kendall, Timothy; Verheij, Joanne; Gaudio, Eugenio; Evert, Matthias; Guido, Maria; Goeppert, Benjamin; Carpino, Guido
Abstract: Cholangiocarcinoma constitutes a heterogeneous group of malignancies that can emerge at any point of the biliary tree. Cholangiocarcinoma is classified into intrahepatic, perihilar and distal based on its anatomical location. Histologically, conventional perihilar/distal cholangiocarcinomas are mucin‐producing adenocarcinomas or papillary tumours; intrahepatic cholangiocarcinomas are more heterogeneous and can be sub‐classified according to the level or size of the displayed bile duct. Cholangiocarcinoma develops through multistep carcinogenesis and is preceded by dysplastic and in situ lesions. Definition and clinical significance of precursor lesions, including biliary intraepithelial neoplasia, intraductal papillary neoplasms of the bile duct, intraductal tubulopapillary neoplasms and mucinous cystic neoplasm, are discussed in this review. A main challenge in diagnosing cholangiocarcinoma is the fact that tumour tissue for histological examination is difficult to obtain. Thus, a major clinical obstacle is the establishment of the correct diagnosis at a tumour stage that is amenable to surgery which still represents the only curable therapeutic option. Current standards, methodology and criteria for diagnosis are discussed. Cholangiocarcinoma represents a heterogeneous tumour with regard to molecular alterations. In intrahepatic subtype, mainly two distinctive morpho‐molecular groups can currently be discriminated. Large‐duct type intrahepatic cholangiocarcinoma shows a high mutation frequency of oncogenes and tumour suppressor genes, such as KRAS and TP53 while Isocitrate Dehydrogenase 1/2 mutations and Fibroblast Growth Factor Receptor 2‐fusions are typically seen in small‐duct type tumours. It is most important to ensure the separation of the given anatomical subtypes and to search for distinct subgroups within the subtypes on a molecular and morphological basis.